Interactivity in Latin American digital journalism. An analysis of the main digital media of Colombia, Mexico and Ecuador (2016) (2017)
Introduction: Latin America, in general terms, is a continent with several contextual levels, which depend on historic, economic, political and social characteristics. Despite all this, there are aspects -such as digital divide- that occur again, to a greater or lesser extent, in the different Latin American countries. This digital divide promotes partially disconnected -and thus, invisible- societies, and tends to slow down possibilities of innovation and development of digital journalism. Methodology: In this study, and from the methodology proposed by Rodríguez, Codina and Pedraza (2012), we have analysed the management of interactivity in the main digital media in Mexico, Colombia and Ecuador in 2016. Results and conclusions: The results show a generally low implementation of interactivity options in digital ecosystems in these three Latin American countries. © 2017, University of La Laguna. All rights reserved.